Peran Guru PAUD Dalam Menstimulasi Perkembangan Bahasa Anak Kelompok B Di TK PGRI 3 Ceria Cendikia Sampang - Rochma Ervina; Anita Mauliyah (Universitas Muhammadiyah Gresik, 2024)
ABSTRACTBased on the results of initial research carried out by the author, the problem in the PGRI 3 Ceria Cendikia Kindergarten, Sokobanah District, Sampang Regency that was discovered in the field was the role of teachers in PAUD in stimulating children's language development in Sampang Regency. From the research results, it can be concluded that the role of PAUD teachers in stimulating the language development of children in group B aged 5-6 years at Kindergarten PGRI 3 Sampang Regency, is that teachers have stimulated children but need to improve it by using various more interesting methods and using different methods. speaking, reading, writing and listening so that children's language development can increase, the language development of children in group B aged 5-6 years at Kindergarten PGRI 3 Sampang Regency by providing examples of teaching stimulation of students' language development so that language development and aspects of language development develop in accordance with child's age stage. Keywords: The Role of Teachers, Language Development, Early Childhood